Turkish board of dermatology and venereology: A survey to identify core curriculum in dermatology and venereology residency training program [Türk dermatoloji yeterlik kurulu dermatoloji uzmanlik eǧitim ulusal çekirdek müfredat oluşturma çalişmasi] - (:unkn) unknown (My University, 2008)
[No abstract available]